ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA PADA MATERI SPLTV DITINJAU DARI GAYA KOGNITIF - Nur Wahyuni Basir; Kristiawati Kristiawati; Muhammad Rizal Usman (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
The main problem in this research is how the students' mathematical reasoning ability on SPLTV material is viewed from the field independent and field dependent cognitive styles. This study aims to describe students' mathematical reasoning abilities on SPLTV material in terms of field independent and field dependent cognitive styles at SMA Muhammadiyah 9 Makassar. The type of research used is descriptive qualitative research. The instruments used are GEFT test, mathematical reasoning ability test and interview guide. The subjects used in this study were 6 students of class X SMA Muhammadiyah 9 Makassar, namely 3 students with field independent cognitive style with high, medium, low mathematical reasoning abilities and 3 students with field dependent cognitive style with high, medium, and medium mathematical reasoning abilities. low in solving problems related to SPLTV material. The results showed that students with field independent cognitive style with high category of mathematical reasoning ability were able to fulfill all indicators well except the ability to check the validity of arguments. Students in the medium category are able to fulfill 3 indicators well, namely the ability to submit conjectures, perform mathematical manipulations, compile evidence and give reasons for the correctness of solutions and are less able to meet the indicators of drawing conclusions. Students in the low category are able to fulfill 2 indicators well, namely the ability to submit conjectures and perform mathematical manipulations, are still lacking in compiling evidence and giving reasons for the correctness of solutions and still lacking in drawing conclusions. Students with field dependent cognitive style with high category mathematical reasoning abilities are able to fulfill 3 indicators of mathematical reasoning well, namely the ability to perform mathematical manipulations, compile evidence for the correctness of solutions and draw conclusions and are quite capable of proposing conjectures. Students in the medium category are able to fulfill 1 indicator well, namely the ability to make conjectures and are quite able to meet 3 indicators of mathematical reasoning ability, namely the ability to perform mathematical manipulations, compile evidence and give reasons for the correctness of solutions and draw conclusions. Students in the low category are still unable to fulfill all indicators of mathematical reasoning abilities except for the fifth indicator, students are not able to check the validity of arguments. Students with field independent and field dependent cognitive styles for the three categories have not been able to fulfill the fifth indicator, namely the ability to check the validity of arguments.